Agronomic performance, proximate composition, zinc and iron contents of biofortified maize hybrids - Iseghohi, O.I.; Ogundare, E.; Fayemiro, S.; Udo, E.; Job, A.; Obisesan, O.; Okonji, C. (2025)
Nutrient deficiency related illnesses are the leading causes of death in developing countries. Maize hybrids biofortified with zinc and iron are key in mitigating African micronutrient deficiencies. Many maize biofortification programmes prioritise micronutrient enrichments, ignoring the attendant effects on grain yield and other macronutrients. This study assessed the agronomic performance, grain yield, and nutrient compositions of selected biofortified maize hybrids. Ten hybrids comprising six candidate hybrids improved for zinc and iron, three commercial hybrids, and one farmer variety were evaluated for two years. Agronomic traits were measured and grain yield estimated. Grain-proximate compositions (%), zinc and iron contents were quantified following standard procedures. Data were analysed using descriptive statistics and ANOVA. Broad-sense heritability and correlation coefficients were estimated. The hybrids differed significantly for grain yield, all agronomic traits, proximate composition, zinc, and iron contents. The overall mean grain yield (t/ha), carbohydrate (%), protein (%), fibre (%), zinc (ug/g), and iron (ug/g) contents were 6.9 ± 0.7, 75.5 ± 0.3, 9.8 ± 0.2, 1.8 ± 0.2, 28.3 ± 0.4 and 28.6 ± 1.9, respectively. Broad-sense heritability ranged from low to high for most agronomic traits but high for nutrient contents, except iron. Plant height, carbohydrate and iron had significant positive relationships with grain yield, while protein had no associations with the micronutrients but was positively correlated with most macronutrients, and carbohydrate had a significant negative association with all the nutrients, except iron. Three candidate hybrids (A2001-1, A2103-24 and A2103-47) had comparable grain yield with the commercial and farmer varieties but outperformed the biofortified check and were superior to two commercial varieties in carbohydrate and iron contents. They are recommended for further testing.